Acupoint catgut embedding: a potential intervention strategy for obesity-related precocious puberty - Liang, Yun; Yuan, Yuan; Yang, Jie (Frontiers in Endocrinology, 2024)
Introduction Obesity-related precocious puberty is induced by obesity, and acupoint catgut embedding (ACE) therapy is known to treat obesity. This study aims to validate the hypothesis that ACE can delay the onset of obesity-related precocious puberty. Methods Female Sprague-Dawley rats, 21 days old, were randomly divided into three groups: the high-fat diet combined with ACE treatment group (ACE), the high-fat diet group (HFD), and the normal control diet group (NCD), with 8 rats in each group. The vaginal opening (VO) time was monitored, and serum levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and total estradiol (E2) were measured, followed by statistical analysis. Results Kaplan-Meier survival curves, with VO as the endpoint, showed that vaginal opening was delayed in the ACE group compared to the HFD group, with a statistically significant difference (p < 0.05). The changes in levels of FSH, LH, and E2 indicated that sexual development was delayed in the ACE group compared to the HFD group and was more similar to the NCD group. Discussion Combining the vaginal opening time and changes in hormone levels, this study confirms the potential role of ACE in delaying the onset of obesity-related precocious puberty.